Perception of depressive symptoms by the Sardinian public: results of a population study - Carta, Mauro Giovanni (BioMed Central, 2013)
BACKGROUND: With the exception of bereavement, the diagnosis of major depressive disorder in the DSM-IV does not take into account the context in which symptoms occur. Recent criticism has maintained that common sense suggests making a distinction between depression as mental disorder and sorrow as ‘normal’ reaction to social stress. Results of a study from Vienna support this view. This study sets out to examine whether these results can be replicated in a different cultural setting. METHODS: In 2012, a population-based survey was conducted by phone in Sardinia (n = 1,200). A fully structured interview was carried out which began with the presentation of a vignette depicting a diagnostically unlabeled case of depression, with or without provision of information about preceding stressful life events. RESULTS: In general, as compared to the people from Vienna, the Sardinian public was much less prone to define depressive symptoms as expression of mental illness and more reluctant to recommend professional help. However, similar to Vienna, respondents presented with vignettes containing information on loss events were less likely to define depressive symptoms as indication of a psychiatric illness. They were also less willing to recommend professional help and relied more on self-help and support by family members and close friends. CONCLUSIONS: We were able to replicate the result of the previous study that the public tends to perceive depressive symptoms differently depending on the context in which they occur. This lets us conclude that the divide between the public’s view of what depression is and the view of DSM-IV is not limited to a particular culture but seems to represent a more general phenomenon. In consequence, one might rethink the diagnostic criteria for major depressive disorder in order to reconcile both views.